Penerapan Konsep Arsitektur Regionalisme pada Bangunan Kampus Universitas Medan Area - Peranita Sagala; Yendi Jhon Frijal Situmorang; Donald Pardede (Universitas Medan Area, 2023)
Indonesia has a distinctive array of architectural styles. Architecture that is rooted in regionalism offers a platform for the revival of traditional design elements in modern structures. One of North Sumatra's first private campuses is that of Medan Area University. The architecture and culture in this region are extremely varied. There is no prevailing architectural style like there is in Riau, West Sumatra, or Java. This campus uses conventional architecture in its construction as it is a university with an architectural study program. The scope of the use of regional architecture on a multicultural campus environment is investigated in this study. Several regional architectural applications have been made using the technique of observation and research of traditional architectural theories of the tribes living in North Sumatra.